Comparative Transcriptome Analysis Reveals New Insight of Alfalfa (Medicago sativa L.) Cultivars in Response to Abrupt Freezing Stress - Wang, Xia; Kang, Wenjuan; Wu, Fang; Miao, Jiamin; Shi, Shangli (Frontiers in Plant Science, 2022)
Freezing stress is a major limiting environmental factor that affects the productivity and distribution of alfalfa (Medicago sativa L.). There is growing evidence that enhancing freezing tolerance through resistance-related genes is one of the most efficient methods for solving this problem, whereas little is known about the complex regulatory mechanism of freezing stress. Herein, we performed transcriptome profiling of the leaves from two genotypes of alfalfa, freezing tolerance ‘Gannong NO.3’ and freezing sensitive ‘WL326GZ’ exposure to -10°C to investigate which resistance-related genes could improve the freezing tolerance. Our results showed that a total of 121,366 genes were identified, and there were 7,245 differentially expressed genes (DEGs) between the control and treated leaves. In particular, the DEGs in ‘Gannong NO.3’ were mainly enriched in the metabolic pathways and biosynthesis of secondary metabolites, and most of the DEGs in ‘WL326GZ’ were enriched in the metabolic pathways, the biosynthesis of secondary metabolites, and plant-pathogen interactions. Moreover, the weighted gene co-expression network analysis (WGCNA) showed that ATP-binding cassette (ABC) C subfamily genes were strongly impacted by freezing stress, indicating that ABCC8 and ABCC3 are critical to develop the freezing tolerance. Moreover, our data revealed that numerous Ca2+ signal transduction and CBF/DREB1 pathway-related genes were severely impacted by the freezing resistance, which is believed to alleviate the damage caused by freezing stress. Altogether, these findings contribute the comprehensive information to understand the molecular mechanism of alfalfa adaptation to freezing stress and further provide functional candidate genes that can adapt to abiotic stress.